1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), §§ 2-3 - (:unkn) unknown (General Publisher, 1927)
Enhanced the sentence of anyone arrested for a crime of violence while being armed with a pistol or revolver. Violators punished with fine of one thousand dollars, or one year in prison, or both. Being armed treated as prima facie evidence of intent to commit said crime of violence.
--
Keywords: CARRY - INTENT TO COMMIT CRIME